Pemberdayaan Masyarakat Melalui Pelatihan Pemasaran Digital Marketing dan Fotografi PKK Padukuhan Karanglo Sedayu Bantul - Asrima, Nuri Pari Julia; Nabila, Silvi; Karindra, Evrilya Deby; Wulan, Nawang; Febrianto, Faisal; Listiyani, Arfina; Andiyansari, Popi; Ahmad, Entus Nuryana; Ahmad, Syukron; Dalili, Dalili (Universitas Islam Negeri Raden Intan Lampung, 2024)
This activity, which is part of the Community Empowerment Communication (KPM) program, aims to improve the ability of PKK members who have MSME products to market their products through